Circle of shadows - Robertson, Imogen, 1973- (Viking, 2013)
When a beautiful aristocrat is murdered during a masked ball in 1784, Mrs. Harriet Westerman and her reclusive companion, anatomist Gabriel Crowther, struggle with reluctant witnesses to clear the name of a falsely accused suspect.